THEORETICAL BASIS FOR THE FORMATION OF THE ORGANIZATION’S STRATEGY - HAVLOVSKA, Nataliia; YOLKIN, Serii; YABLONSKY, Taras; NEBELUK, Nazarii (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines the evolution of strategic management, which consists of five stages: budgeting and control, long-term planning, strategic planning, strategic management (strategic management), strategic management based on flexibility. The first stage - budgeting and control - involves the development of annual budgets, followed by the analysis of deviations, their causes, and, if necessary, makes decisions about adjustments, the second stage - long-term planning - it is assumed that the trends that were in the past will continue in the future, that is, on based on retrospective data and past experience, the third stage – strategic planning focused on the market environment, the fourth stage – strategic management (strategic management) – takes into account the dynamism of the external environment, therefore cyclical planning is not applied. The first four stages are proposed by David Aaker with the author’s addition, and the fifth is rejected by us as a modern approach to strategic planning, since strategic management on the basis of flexibility is a need of the modern stage of enterprise functioning, and is based on the use of agile methods, as well as technologies and tools capable of processing a large array of information and learning. The article examines the essence of the concept of "strategy". The study of various approaches and existing opinions made it possible to form the author’s view on the category "strategy", that is, the strategy should be understood as a long-term direction of activity formed on the basis of an objective assessment of the external and internal environment, the resources of the organization, and oriented towards meeting the requirements of interested parties, development and continuous improvement of activities. Strategic management of the development of the organization is based on the choice of strategy depending on the goals and directions of development, so the article provides a hierarchy of the company’s strategies. Types of corporate, competitive and functional strategies are given.